Technologies and Trends to Improve Table Olive Quality and Safety - Campus, Marco; Değirmencioğlu, Nurcan; Comunian, Roberta (Frontiers in Microbiology, 2018)
Table olives are the most widely consumed fermented food in the Mediterranean countries. Peculiar processing technologies are used to process olives, which are aimed at the debittering of the fruits and improvement of their sensory characteristics, ensuring safety of consumption at the same time. Processors demand for novel techniques to improve industrial performances, while consumers’ attention for natural and healthy foods has increased in recent years. From field to table, new techniques have been developed to decrease microbial load of potential spoilage microorganisms, improve fermentation kinetics and ensure safety of consumption of the packed products. This review article depicts current technologies and recent advances in the processing technology of table olives. Attention has been paid on pre processing technologies, some of which are still under-researched, expecially physical techniques, such ad ionizing radiations, ultrasounds and electrolyzed water solutions, which are interesting also to ensure pesticide decontamination. The selections and use of starter cultures have been extensively reviewed, particularly the characterization of Lactic Acid Bacteria and Yeasts to fasten and safely drive the fermentation process. The selection and use of probiotic strains to address the request for functional foods has been reported, along with salt reduction strategies to address health concerns, associated with table olives consumption. In this respect, probiotics enriched table olives and strategies to reduce sodium intake are the main topics discussed. New processing technologies and post packaging interventions to extend the shelf life are illustrated, and main findings in modified atmosphere packaging, high pressure processing and biopreservaton applied to table olive, are reported and discussed.